If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(m-24)(m+24)=100
We move all terms to the left:
(m-24)(m+24)-(100)=0
We use the square of the difference formula
m^2-576-100=0
We add all the numbers together, and all the variables
m^2-676=0
a = 1; b = 0; c = -676;
Δ = b2-4ac
Δ = 02-4·1·(-676)
Δ = 2704
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{2704}=52$$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-52}{2*1}=\frac{-52}{2} =-26 $$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+52}{2*1}=\frac{52}{2} =26 $
| 94+x+93+x+77=360 | | 4(w+7)=-2(4w-6)+6w | | (x-11)•-4=-48 | | x+6=27+4x | | 68+64+90+2x=360 | | 100+x+24+89+68=360 | | x/x-1+1/x=3 | | 7p-(3p+4)=-2(2p-1p)+10 | | 2x=180,x=90 | | 60+x+3+64+x+33=360 | | 21/5y=66 | | X=6,x=-6 | | -67=-8n | | -3/5k=(-9) | | 10+4x=2x+18 | | 3(b+6)+2=14 | | -d/4-1=-6 | | 2x+x+69+72=360 | | 5(10-a)=25 | | 11x+8=-2(-5x-4 | | 3x(x-1)(x-2)=00=x | | N=1/8,2/n= | | -1g+2(3+1g)=-4(1g+1 | | p/1.2=10.5 | | 7(u+3)=-3(2u-5)+9u | | (5-2)+0.2=n | | 2x+19+x=90 | | -8=x-7-6 | | -4b-5b=-16-b | | (9.3)/n)-1=8.3 | | 12•2^x-^7=24 | | -g+2(3+g)=-4(1g+1 |